Rasio Keuangan dan Return Saham Syariah - Dyah Putri Widyarini; Muhammad Arsyadi Ridha (Al-Tijary, 2019)
This study investigates the effect of financial ratios on stock returns at companies listed in Indeks Saham Syariah Indonesia (ISSI) period 2012-2016. This study uses quantitative methods with secondary data collected from the company's financial statements. The population in this study were all companies listed on the Syariah Indonesia Stock Index (ISSI) during the period of 2012-2016 as many as 149 companies. Based on the sampling technique with purposive sampling method obtained a sample of 59 companies with data collected during the period 2012-2016 as many as 295 financial report data. In this study panel panel regression was used to see the effect of the independent variables consisting of ROCE, TATO, TIER, PER and CFR on the dependent variable namely Stock Return. Processing data in this study using Eviews 9. Software. Data analysis techniques in this study using statistical techniques with the help of Eviews 9 program.  Based on 59 companies observed, fixed effect panel data regression models have been used to examine the relevance to the effect of financial ratios on stock returns. The result of the research, found that the Total Asset Turnover (TATO) and Time Interest Income Ratio (TIER) have a positive effect on stock returns. Total Asset Turnover (TATO) and Time Interest Earned Ratio (TIER) can be considered by investors to make decisions in choosing which companies have high stock returns. Return On Capital Employed (ROCE), Price To Earning Ratio (PER), and Cash Flow Ratio (CFR) are not related to stock returns.